Sjúkdómsvaldandi örverur í grunnvatni - Sigurður Magnús Garðarsson 1967-; María J. Gunnarsdóttir 1947-; Hrund Ólöf Andradóttir 1972- (2008)
Ritrýnd vísindagrein í Árbók Verkfræðingafélagsins 2008 The aim of this study is to evaluate transport of pathogens in groundwater under Icelandic hydrological conditions.This is done by using an outbreak of Norovirus that occurred in northern Iceland in the summer 2004. The outbreak was confirmed to come from a septic tank some 80 m from the water well. Calculation shows that there was little danger of bacteriological contamination being carried by groundwater to the site, but that viruses could be transmitted to the water well.To prevent the contaminant from reaching the well the septic tank should have been at least 200 m from the well.